Framework para gestão dos processos de reciclagem dos sistemas de armazenamento de energia dos veículos elétricos - Sidrim, Alexandre Stephan da Silva (2024)
The management of recycling of electric vehicle energy storage systems is an important topic that has received increasing attention in recent years. Proper management of battery recycling, which involves monitoring, maintenance, reuse and recycling, is essential to maximize the useful life of these modern vehicles’ energy storage systems, minimize environmental impacts and ensure user safety. This includes monitoring the performance of batteries throughout their useful life, performing appropriate maintenance, exploring options for reuse, recycling and responsible disposal. Therefore, this research had the general objective of proposing a framework for managing the recycling processes of Electric Vehicle energy storage systems. Methodologically, the dissertation was supported by bibliographical and documentary research and research carried out with specialists in related areas. After completing the Systematic Literature Review, the social, economic, political, environmental, and technological aspects related to the recycling of these systems were identified and analyzed. Subsequently, responses from quantitative and qualitative questions carried out in a survey among experts were compiled, and in line with the results obtained, a comprehensive framework was drawn up. The contribution of this research to the proposal for efficient and sustainable recycling management stands out. The results will enable the expansion of knowledge on the subject, promoting significant contributions to both the academic and business spheres.